Efficacy and role of vitamin D (25-OH-D serum) in the treatment of endometriosis: A systematic review - Diani, Yuli Ayu; Wiyasa, I Wayan Arsana (Majalah Obstetri & Ginekologi, 2025)
HIGHLIGHTS Endometriosis frequently causes pelvic damage and infertility, and vitamin D has been proposed as a therapeutic option owing to its involvement in immune regulation and reproductive health. Vitamin D may contribute to the modulation of inflammatory pathways and decrease the risk of hyperplasia and malignancy, with several studies indicating that it might also impact infertility related to endometriosis. ABSTRACT Objective: Vitamin D, an essential element in women’s reproductive health, has shown potential benefits in endometriosis management by improving plasma concentrations and modulating immune responses in chronic inflammatory conditions, including endometriosis. This study aimed to elucidate the pivotal role of vitamin D in alleviating chronic pain and infertility associated with endometriosis and to provide new insights into its therapeutic application in reproductive medicine. Materials and Methods: This systematic review examined literature retrieved from PubMed, ScienceDirect, ResearchGate, and Google Scholar, screening 1,156 records and including 20 studies for qualitative assessment. The review focused on the therapeutic contribution of vitamin D in endometriosis management. Eligible studies were those published in the last decade, in English, involving non-pregnant, healthy women, particularly patients with chronic pelvic pain or infertility. Accepted study designs comprised experimental, cohort, longitudinal, case reports, pilot, and observational studies. Excluded were non-English articles, animal or pregnant populations, reviews, inaccessible full texts, and studies lacking relevance to vitamin D or endometriosis. Results: Twenty selected studies were analyzed, encompassing 5,346 women and 60 girls aged 12–50 years, with or without endometriosis, from Iran, the USA, South Korea, Russia, Turkey, Brazil, Poland, Italy, Germany, and Japan. These studies indicated that multiple therapeutic approaches were attempted, suggesting that endometriosis may be partially ameliorated by vitamin D administration. Conclusion: This systematic review highlights that women with endometriosis presented with lower vitamin D levels; however, the evidence regarding supplementation efficacy remains uncertain. Further large-scale, rigorously designed trials are necessary to establish vitamin D’s therapeutic role in the management of endometriosis.